2018
DOI: 10.1177/0391398818785132
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of red blood cell transfusion and its association with prognosis in patients undergoing extracorporeal membrane oxygenation

Abstract: This study suggests that red blood cell transfusion may be associated with a higher mortality rate and with severe complications. However, we cannot conclude a direct causal relationship, as red blood cell transfusion may be only a marker of poor outcome. We recommend that physicians correct acidosis and hemolysis in patients undergoing extracorporeal membrane oxygenation whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…These patients required significantly higher amounts of blood products (by a factor of 2.5 more RBCs) and tended to a higher proportion of ARF during ECMO. Another retrospective study from [25] demonstrated that RBC transfusion during ECMO was associated with severe complications (thromboembolic complications, sepsis, hemolysis) and ARF. Red cell damage during storage and the potential harmful consequences after transfusion are discussed in literature-in particular in massive transfusion scenarios [26].…”
Section: Discussionmentioning
confidence: 99%
“…These patients required significantly higher amounts of blood products (by a factor of 2.5 more RBCs) and tended to a higher proportion of ARF during ECMO. Another retrospective study from [25] demonstrated that RBC transfusion during ECMO was associated with severe complications (thromboembolic complications, sepsis, hemolysis) and ARF. Red cell damage during storage and the potential harmful consequences after transfusion are discussed in literature-in particular in massive transfusion scenarios [26].…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Consequently, the adoption of more restrictive transfusion protocols, inferred from the lower accepted Hb, may be one of the contributing factors in higher survival and better clinical outcomes. 40…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of the immune response by transfusion may promote the development of postoperative infectious complications [24,25]. A transfusion in patients supported with VA-ECMO is also known to increase infectious complications [26]. In the present study, beyond the risk associated with low cardiac output and surgical reoperation itself, 34% of HTx recipients received a postoperative transfusion despite a restrictive strategy of blood transfusion in our institution, thereby increasing the risk of postoperative pneumonia.…”
Section: Non-documented Infections 2 (2)mentioning
confidence: 66%